2020
DOI: 10.1097/ccm.0000000000004285
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord-Derived Mesenchymal Stem Cells for Acute Respiratory Distress Syndrome

Abstract: Objectives: To investigate the safety, feasibility, and possible adverse events of single-dose human umbilical cord-derived mesenchymal stem cells in patients with moderate-to-severe acute respiratory distress syndrome. Design: Prospective phase I clinical trial. Setting: Medical center in Kaohsiung, Taiwan. Patients: Moderate-to-severe acute respiratory distress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 35 publications
5
83
0
Order By: Relevance
“…27 The average age of study participants was 51 to 67 years for the MSC groups and 55 to 70 years for the control groups in the comparative studies. Baseline PaO 2 /FiO 2 was in a range of 100 to 200 in six studies [21][22][23][24][25]27 and not reported in two studies in which all patients were on ventilator or extracorporeal membrane oxygenation (ECMO) support. 26,28 Baseline Acute Physiology and Chronic Health Evaluation (APACHE) scores were between 23 and 27 in one study, 22 averaged 108 in one study, 21 and 104 in the MSC group vs 89 in the control group in one study 24 (Table 1).…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…27 The average age of study participants was 51 to 67 years for the MSC groups and 55 to 70 years for the control groups in the comparative studies. Baseline PaO 2 /FiO 2 was in a range of 100 to 200 in six studies [21][22][23][24][25]27 and not reported in two studies in which all patients were on ventilator or extracorporeal membrane oxygenation (ECMO) support. 26,28 Baseline Acute Physiology and Chronic Health Evaluation (APACHE) scores were between 23 and 27 in one study, 22 averaged 108 in one study, 21 and 104 in the MSC group vs 89 in the control group in one study 24 (Table 1).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The studies were from six countries and regions, including China (n = 3), 20,22,26 the United States (n = 2), 21,24 United States/United Kingdom (n = 1), 23 Sweden (n = 1), 28 Taiwan (n = 1), 25 and South Korea (n = 1). 27 The average age of study participants was 51 to 67 years for the MSC groups and 55 to 70 years for the control groups in the comparative studies.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations